The effect of noise intensity on parabolic equations - Jiang-lun Wu (Discrete & Continuous Dynamical Systems - B, 2020)
In this paper, the effect of noise intensity on parabolic equations is considered. We focus on the effect of noise on the energy solutions of stochastic parabolic equations. By utilising Ito’s formula and energy estimate method, we obtain excitation indices of the solution u at time t. Furthermore, we verify the existing results in the literature by a comparably simpler method.